2017
DOI: 10.15184/aqy.2017.141
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the layout of early coastal settlement at Unguja Ukuu, Zanzibar

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Zooarchaeological and archaeobotanical records from these sites indicate a preference for hunting wild fauna while crops are extremely rare [ 1 , 17 , 27 , 91 ]. By contrast, village sites including Fukuchani, Membeni, Sima and Unguja Ukuu comprised small- to medium-sized settlements with mainly daub dwellings (though stone structures are also present at Unguja Ukuu) [ 92 , 93 ]. These were occupied by communities with mixed subsistence economies that included hunting, fishing and crop cultivation [ 2 , 11 , 27 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Zooarchaeological and archaeobotanical records from these sites indicate a preference for hunting wild fauna while crops are extremely rare [ 1 , 17 , 27 , 91 ]. By contrast, village sites including Fukuchani, Membeni, Sima and Unguja Ukuu comprised small- to medium-sized settlements with mainly daub dwellings (though stone structures are also present at Unguja Ukuu) [ 92 , 93 ]. These were occupied by communities with mixed subsistence economies that included hunting, fishing and crop cultivation [ 2 , 11 , 27 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Contemporaneous with Kuumbi's reoccupation included the appearance of small villages across the archipelago such as Fukuchani in north Unguja, and trading ports such as Unguja Ukuu in the south (Juma, 2004). This period was characterised by the rise of Indian Ocean trade on the Swahili coast, linking it with China, South Asia, and the Middle East (e.g., Juma, 2004;LaViolette, 2008;Wood et al, 2016), as well as the introduction of Islam (Crowther et al, 2015;Fitton and Wynne-Jones, 2017;Sarathi et al, 2022).…”
Section: Archaeological and Historical Overviewmentioning
confidence: 99%
“…Research on the immediate foreshore near Swahili sites has revealed a range of maritime adaptations around Kilwa, Songo Mnara and Bagamoyo in Tanzania, and Gede in Kenya [75,[82][83][84][85] (Figure 2). A geophysical survey on the Zanzibar archipelago explored the shorelines of settlements and demonstrated the range of industry and activity associated with this zone [86]. On Madagascar, excavations on the coast have shown the long temporal depth of coastal resource exploitation here [87].…”
Section: Uniting Terrestrial and Maritime Researchmentioning
confidence: 99%